2015
DOI: 10.1306/10081413128
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-induced diagenetic alteration of the Permian White Rim Sandstone, Elaterite Basin, southeast Utah

Abstract: Sandstone is well exposed and varies in color from white to red, orange, and brown. Superimposed on eolian and marine deposits are three diagenetic facies that impart the coloration and are defined by iron oxide cement concentration as (1) bleached white (low iron), (2) diffuse (moderate iron), and (3) concretionary (concentrated iron). A yellow alteration aureole of bleaching extends up to 10 m (32 ft) into the underlying Organ Rock Shale and up to 20 m (65 ft) into the overlying Moenkopi Formation. These for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…; Parry et al . ; Gorenc & Chan ). The chemical reduction in ferric iron and bleaching also result in reduction in aqueous sulfate to sulfide and precipitation of pyrite.…”
Section: Evidence For Hydrocarbon Migration During the Mineralizationmentioning
confidence: 98%
“…; Parry et al . ; Gorenc & Chan ). The chemical reduction in ferric iron and bleaching also result in reduction in aqueous sulfate to sulfide and precipitation of pyrite.…”
Section: Evidence For Hydrocarbon Migration During the Mineralizationmentioning
confidence: 98%
“…Notable examples of white sandstone facies are found in the Jurassic Navajo Sandstone and Permian White Rim Sandstone in Southeastern Utah (USA), and in the Buntsandstein and Rotliegend sandstones in Central Germany, where white sandstone beds are surrounded by red sandstone beds [51][52][53]95,96].…”
Section: Origin Of White Sandstonementioning
confidence: 99%
“…In addition, we report the occurrence of a peculiar white sandstone that is commonly associated with CM rocks in the study area. White sandstone facies has been reported in Southeastern Utah and central Germany [50][51][52][53], and it was suggested that it might have originated from the bleaching process of an original red sandstone protolith. Moreover, some researchers also proposed that the white sandstone in the northeastern Ordos basin derived from bleaching of an original red sandstone [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…In the western USA, long range migration through extensive Permo-Pennsylvanian aeolian dune reservoirs is well documented (Claypool et al 1978 ;Gorenc and Chan 2015 ;Hansley 1995 ;Huntoon et al 1994Huntoon et al , 1999Maughan 1984Maughan , 1994. Figure 9.3 summarizes the distribution of source rocks that could potentially charge the Permo-Pennsylvanian reservoirs and locations of major traps in Wyoming and Utah.…”
Section: Long Range Migrationmentioning
confidence: 99%